Somatogenic and somatogenically provoked psychoses in blood diseases - D É Vybornykh; S V Ivanov; V G Savchenko; É G Gemdzhian (Терапевтический архив, 2008)
Aim. To detect risk factors (RF) to develop somatogenic psychoses (SP) in blood diseases. Material and methods. A total of 107 SP patients were examined with the disease corresponding to diagnostic points F05 or F06 (IDC-10). Results. The following RF were identified: cytostatic drugs with or without glucocorticosteroids, glucocorticosteroids alone, interferon-alpha, viral encephalitis, neuroleukemia. Single obligatory specific factors which bring manifestation of certain psychoses were not identified. SP in each of the considered hematological malignancies are related with various factors. Conclusion. The findings suggest polyfactor etiology of SP including some schemes of chemotherapy, some type of blood disease, specific premorbid features and mental disease burden. We suggest that the clinical picture, dynamics and prognosis of SP in blood diseases may be caused by a profile of factors typical for each disease.